Community perception of corporate environmental policy implementation in nickel mining in Indonesia - Citra Tri Rahmawati; Evi Frimawaty; Soemarno Witoro Soelarno (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Morowali Regency, Central Sulawesi, is rich in nickel deposits and has generated significant economic benefits through the government's downstreaming policy. However, its environmental and social impacts on surrounding communities remain subjects of ongoing concern. This study examines community perceptions of the environmental policies of Company X, a nickel mining company operating in Tangofa Village, Bungku Pesisir District. Methods: A quantitative approach was employed using a structured questionnaire administered to 101 respondents through purposive sampling based on specific inclusion criteria. Data were analyzed using descriptive statistics, normality testing (Kolmogorov-Smirnov), Spearman rank correlation, and multiple linear regression. Findings: Community perceptions of economic aspects were rated highest, driven by local employment absorption and household income improvement. Social aspects received a positive rating, though challenges remain regarding community dependency on corporate assistance programs. Environmental aspects received the lowest rating, with air and water quality scoring in the Poor category. Regression analysis confirms that the social factor is the most dominant predictor (β = 0.772; p < 0.001), while Economic and Environmental factors exhibited significant negative influences on the Environmental Policy implementation variable (β = −0.125; p < 0.02). Conclusion: Community acceptance of Company X's environmental policy is primarily driven by social dynamics rather than economic or environmental outcomes. The findings highlight a persistent gap between procedural environmental engagement and substantive environmental quality improvement. Novelty/Originality of this article: This study contributes a community-based perception framework for evaluating corporate environmental policy implementation in the nickel mining sector within the context of Indonesia's national downstreaming strategy, integrating sustainable development dimensions into a quantitative assessment model.